Molecular Systematics of the Genus Acidithiobacillus: Insights into the Phylogenetic Structure and Diversification of the Taxon - Nuñez, Harold; Moya-Beltrán, Ana; Covarrubias, Paulo C.; Issotta, Francisco; Cárdenas, Juan Pablo; González, Mónica; Atavales, Joaquín; Acuña, Lillian G.; Johnson, D. Barrie; Quatrini, Raquel (Frontiers in Microbiology, 2017)
The acidithiobacilli are sulfur-oxidizing acidophilic bacteria that thrive in both natural and anthropogenic low pH environments. They contribute to processes that lead to the generation of acid rock drainage in several different geoclimatic contexts, and their properties have long been harnessed for the biotechnological processing of minerals. Presently, the genus is composed of seven validated species, described between 1922 and 2015: Acidithiobacillus thiooxidans, A. ferrooxidans, A. albertensis, A. caldus, A. ferrivorans, A. ferridurans and A. ferriphilus. However, a large number of Acidithiobacillus strains and sequence clones have been obtained from a variety of ecological niches over the years, and many isolates are thought to vary in phenotypic properties and cognate genetic traits. Moreover, many isolates remain unclassified and several conflicting specific assignments muddle the picture from an evolutionary standpoint. Here we revise the phylogenetic relationships within this species complex and determine the phylogenetic species boundaries using three different typing approaches with varying degrees of resolution: 16S rRNA gene-based ribotyping, oligotyping, and multi-locus sequencing analysis (MLSA). To this end, the 580 16S rRNA gene sequences affiliated to the Acidithiobacillus spp. were collected from public and private databases and subjected to a comprehensive phylogenetic analysis. Oligotyping was used to profile high-entropy nucleotide positions and resolve meaningful differences between closely related strains at the 16S rRNA gene level. Due to its greater discriminatory power, MLSA was used as a proxy for genome-wide divergence in a smaller but representative set of strains. Results obtained indicate that there is still considerable unexplored diversity within this genus. At least six new lineages or phylotypes, supported by the different methods used herein, are evident within the Acidithiobacillus species complex. Although the diagnostic characteristics of these subgroups of strains are as yet unresolved, correlations to specific metadata hint to the mechanisms behind econiche-driven divergence of some of the species/phylotypes identified. The emerging phylogenetic structure for the genus outlined in this study can be used to guide isolate selection for future population genomics and evolutionary studies in this important acidophile model.